(untitled) (Research, Society and Development, 2020)
The use of irrigation in a consortium between cowpea and corn is a profitable alternative to meet the demand for food. In this sense, the objective was to evaluate the productivity of the cowpea and corn consortium, under different irrigation depths and dead vegetation cover. The study was carried out in the experimental area of the Agrometeorological Station, at the Federal University of Ceará (UFC), from August to December 2018. A randomized block design was used in subdivided plots, in a 5 x 4 factorial arrangement, referring to five irrigation depths (25%, 50%, 75%, 100% and 125% of the consortium evapotranspiration - ETc) and four types of dead vegetable coverings (rice husk, carnauba straw, mixed and without cover), with four repetitions. The number and length of pods per plant and the productivity for the cowpea culture and the length and mass of the cob with straw and the productivity for the corn culture were evaluated. The effect of the interaction of dead vegetable coverings, rice husk and mixed, depending on the irrigation depths provided a significant increase in the number of pods per plant, ear length, ear mass with straw and productivity of cowpea and corn crops for the irrigation depths equivalent to 125% of the ETc.